The Influence of Zeolite Addition into Anaerobic Vinasse Treatment Process in Microaerated Batch Reactor: Pengaruh Penambahan Zeolit Pada Pengolahan Limbah Vinasse secara Anaerob dalam Reaktor Batch Dengan Mikroaerasi - Umul Lailatul Jannah; Gregorius Prima Indra Budianto (Program Studi S1 Teknik Kimia, Fakultas Teknik, Universitas Setia Budi, 2020)
Microaeration and cell immobilization are two ways to improve the performance of vinasse anaerobic treatment. Several variations of vinasse anaerobic process were conducted to approach the effectivity of microaeration and cell immobilization addition in 200 ppm vinasse anaerobic treatment process. The variation of (R1) microaeration addition; (R2) zeolite addition as cell immobilizer; (R3) combination microaeration and zeolite addition and (R4) blank reactor – anaerobic reactor without microaeration and zeolite addition. The process was conducted in batch mode, pH in 7. During the process, gas volume was calculated by water replacement concept and sampling was done for analytical such as Volatile Solids (VS) and methane concentration. The result, combination between microaeration and zeolite addition was obtained the lag phase to be shorter while the biogas productivity and VS degradation rate were obtained the insignificant difference value with reactor with zeolite addition and reactor with microaeration addition respectively. Abstrak Beberapa variasi proses dilakukan untuk menakar sejauh mana efektifitas mikroaerasi dan imobilisasai sel pada proses pengolahan limbah vinasse 200 ppm secara anaerob, variasi tersebut diantaranya (R1) reactor dengan mikroaerasi, (R2) reactor dengan penambahan zeolite, (R3) reactor dengan penambahan mikoraerasi dan zeolite (R4) reactor control – tanpa penambahan mikroaerasi dan zeolite. Proses dijalankan pada kondisi pH 7, mode batch. Selama proses, pengukuran volume biogas dilakukan dengan konsep water replacement dan pengambilan sampel dilakukan untuk kebutuhan analisis Volatile Solids (VS) dan kadar metana. Hasilnya, penambahan zeolite pada reactor dengan mikroaerasi menghasilkan masa aklimatisasi tersingkat sedangkan produktivitas dan laju penunuran VS tidak berbeda signifikan masing-masing dari reactor dengan zeolite dan reactor dengan mikroaerasi.